2017
DOI: 10.1007/s10803-017-3303-1
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Specialist Mentoring for University Students with Autism Spectrum Disorders and Mental Health Conditions

Abstract: Mentoring is often recommended to universities as a way of supporting students with Autism Spectrum Disorders (ASD) and/or mental health conditions (MHC), but there is little literature on optimising this support. We used mixed-methods to evaluate mentees' and mentors' experiences of a specialist mentoring programme. Mentees experienced academic, social and emotional support, although subtle group differences emerged between students with ASD and MHC. The quality of the mentee-mentor relationship was especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Recent reports suggest that although around half (46%) of autistic students have the intellectual potential (Centers for Disease Control and Prevention 2012) to attend higher education (Sanford et al 2011), the number of enrolment, retention, academic achievements, and employment rate following graduation is still relatively lower compared to students with other disabilities, as well as their typically developing peers (AGCAS Disability Task Group 2014; Gobbo and Shmulsky 2014;Lucas and James 2018). A recent report (Jackson et al 2018) also found in a sample of 56 autistic adults currently enrolled in post-secondary institutions in the US, UK, and Canada, around three quarters reported feelings of isolation, high levels of stress, anxiety, depression, and suicidal ideation, further highlighting the poor state of mental health for many autistic students when transitioning to university.…”
mentioning
confidence: 99%
“…Recent reports suggest that although around half (46%) of autistic students have the intellectual potential (Centers for Disease Control and Prevention 2012) to attend higher education (Sanford et al 2011), the number of enrolment, retention, academic achievements, and employment rate following graduation is still relatively lower compared to students with other disabilities, as well as their typically developing peers (AGCAS Disability Task Group 2014; Gobbo and Shmulsky 2014;Lucas and James 2018). A recent report (Jackson et al 2018) also found in a sample of 56 autistic adults currently enrolled in post-secondary institutions in the US, UK, and Canada, around three quarters reported feelings of isolation, high levels of stress, anxiety, depression, and suicidal ideation, further highlighting the poor state of mental health for many autistic students when transitioning to university.…”
mentioning
confidence: 99%
“…Mentoring has also been examined in the context of social-emotional supports for students with ASD in postsecondary environments. Lucas and James [74] tested the effect of a mentoring program for three undergraduate students with ASD and two with mental health conditions. After the first term, mentees with ASD expressed that mentors had been helpful for exam support, maintenance and development of social relationships, and promotion of positive well-being, while mentees with mental health issues did not find mentors as helpful in these areas.…”
Section: Transitioning To the Universitymentioning
confidence: 99%
“…Lucas and James (2018) evaluate a specialist mentoring program that examines benefits for students with ASD as well as students with mental health conditions, and utilizes a mixed-methods methodology incorporating feedback from the mentors and the mentees (Lucas and James 2018). The inclusion of the mental health condition control group not only offers the opportunity to elucidate benefits that may be specific to the needs of students with ASD, but considering the high occurrence of mental health issues reported in the and Anderson et al reports, a service that can cater to both of these conditions will have utility for the majority of college students with ASD.…”
mentioning
confidence: 99%